Exploring a language learning history: The journey of self-discovery from the perspectives of individual differences - Naoya Shibata (Universitas Islam Malang, 2020)
Exploring a language learning history can help researchers, teachers, and students to reveal and understand various individual difference factors which positively or negatively influence language learning activities and strategy use. In this paper, I examined my English language learning history and delved into challenges and factors to overcome them and activate my autonomy. Based on the analysis of my learning history, three main themes were indicated: a) motivational shifts and goal-setting theory, b) learning beliefs and goal setting, and c) the relationship between learning strategy use and teachers’ influence. Furthermore, my learning history also illustrated that I tended to change all these features through both successful and unsuccessful experiences. Among them, goal-setting seems to be the most significant factor for me to study the target language. With clear learning objectives, I overcame many challenges and sustained high motivation by utilising various types of learning strategies and having positive learner beliefs. Accordingly, noticeable relationships among motivation, learner belief, and learning strategy use were revealed through my learning history log.